Earthworm immunity - Bilej, Martin; Procházková, Petra; Silerová, Marcela; Josková, Radka (Advances in experimental medicine and biology, 2010)
Earthworms belonging to oligochaete annelids became a model for comparative immunologists in the early sixties with the publication of results from transplantation experiments that proved the existence of self/nonself recognition in earthworms. This initiated extensive studies on the earthworm immune mechanisms that evolved to prevent the invasion of pathogens. In the last four decades important cellular and humoral pathways were described and numerous biologically active compounds were characterized and often cloned.
Keywords: buněčná imunita; Oligochaeta; zvířata; Immunity, Cellular; humorální imunita; Immunity, Humoral; Animals